ATTITUDES TOWARDS EXERCISE AND THE PHYSICAL EXERCISE HABITS OF UNIVERSITY OF ZAGREB STUDENTS - Zoran Milanović; Goran Sporiš; Nebojša Trajković; Dalibor Vračan; Mirna Andrijašević; Saša Pantelić; Mario Baić (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2013)
The aims of this research were to determine the importance that university students give physical activity, to distinguish those sport activities that university students prefer and would want to be involved in, and to determine the differences in attitude towards individual sports activities in regard to gender. The study was conducted using a sample of 190 (age 18 +-1 year) randomly selected university students (108 females; 82 males) that are currently attending the first and second year of architecture and geodesy and who also attend physical education classes. The results showed that university students were very well informed about the importance of physical exercise and recreation. Nevertheless, when it came to their involvement in various sporting activities, the questionnaires showed that almost 57 % of the university students do not generally spend their time participating in any sports and recreational activities. On the other hand, statistically significant differences (p > 0.00) were found between men and women in terms of selection and participation in sport activities based on the completed questionnaire. Based on the obtained data, the university students were offered sport events consistent with sports trends, following the wishes and interests of specific groups with regard to gender.